Microstructure evolution and mechanical properties of TiB/Ti6Al4V composites based on selective laser melting - Huang, Xu; Zhu, Yitao; Huang, Weidong; Wang, Lu (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
To study the strengthening mechanism of TiB/Ti6Al4V composites prepared by SLM and the control method of the energy density on the microstructure and mechanical properties, in this paper, Ti6Al4V+3wt.% TiB2 composite powder was used as a raw material to synthesize TiB in situ and prepare TiB/Ti6Al4V whisker-reinforced composites. The effect of the energy density on the forming properties, microstructure evolution and mechanical properties of TiB/Ti6Al4V was systematically studied, and the formation, regulation and strengthening mechanism of TiB whiskers were discussed. The results show that during the SLM process, adjusting the energy density can effectively inhibit the occurrence of cracks in the TiB/Ti6Al4V samples. The added TiB2 acts as a nucleation center to significantly refine the grains during the forming process and reacts with Ti to form a needle-like TiB network structure at the grain boundary, strengthening the whiskers. Additionally, TiB plays a role in dispersion strengthening. Compared with Ti6Al4V, the microhardness of TiB/Ti6Al4V reaches 430.6±11.45HV, an increase of 27.9%, and the wear volume of the sample is 0.85×10-3 mm3, a decrease of 62.64%.